Uso de herramientas TIC en el desempeño laboral del área administrativa de la Cooperativa de Ahorro y Crédito Sierra Centro Latacunga. - Lema Quishpe, Daysi Maribel (2023)
Currently, the use of TIC is important within organizations because it allows to generate greater productivity and help in work performance. This research work was developed in the Savings and Credit Cooperative "Sierra Centro Latacunga", aims to propose TIC tools to help strengthen the work performance of collaborators focusing on the tactical and operational level, a quantitative methodology was applied, with a descriptive level and a non-experimental design with a cross-sectional or transactional study, data collection was done through the application of a questionnaire validated by 3 teachers specialized in the subject, consists of 6 dimensions that are: technology, equipment and infrastructure, communication, planning, storage, work performance and has 23 items with a rating scale from 1 to 5 This questionnaire was applied in person to 25 collaborators of the institution. The results obtained by taking into consideration the 6 dimensions of the questionnaire showed that there are shared opinions of the workers, approximately more than half of the workers are satisfied with the tools provided by the institution, however, about 40% of the collaborators stated that the cooperative does not have sufficient information and communication technologies to carry out daily activities, for this reason, several technological tools were analyzed in order to propose those that best meet the needs of the personnel in order to achieve 100% satisfaction.